2016
DOI: 10.1016/j.jtcme.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic administration of an extract from Plantaginis Semen and its major component aucubin inhibits mechanical allodynia caused by paclitaxel in mice

Abstract: The chemotherapeutic agent paclitaxel (PTX) causes peripheral neuropathy as a major dose-limiting side effect, and this peripheral neuropathy is difficult to control. Our previous report showed that prophylactic repetitive administration of goshajinkigan (牛車腎氣丸 niú chē shèn qì wán), but not hachimijiogan (八味地黃丸 bā wèi dì huáng wán), which lacks two of the constituents of goshajinkigan, inhibited PTX-induced mechanical allodynia in mice. Thus, the herbal medicines Plantaginis Semen (車前子 chē qián zǐ) or Achyrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Seven GJG, an aqueous extract of a combination of 10 herbs, is widely used in Japan for the treatment of lumbago, edema of the lower extremities, numbness, blurred vision, lower urinary tract symptoms, diabetic neuropathy and pain in people with diminished physical strength 9) . Recently, preventive effects of oral GJG on chronic oxaliplatin-induced hypoesthesia 10) and paclitaxel induced allodynia 11) in animal models were reported. Clinically, GJG could show the preventive effect of paclitaxel induced peripheral neuropathy for patients with ovarian or endometrial cancer who underwent chemotherapy by a multicenter study 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Seven GJG, an aqueous extract of a combination of 10 herbs, is widely used in Japan for the treatment of lumbago, edema of the lower extremities, numbness, blurred vision, lower urinary tract symptoms, diabetic neuropathy and pain in people with diminished physical strength 9) . Recently, preventive effects of oral GJG on chronic oxaliplatin-induced hypoesthesia 10) and paclitaxel induced allodynia 11) in animal models were reported. Clinically, GJG could show the preventive effect of paclitaxel induced peripheral neuropathy for patients with ovarian or endometrial cancer who underwent chemotherapy by a multicenter study 12) .…”
Section: Discussionmentioning
confidence: 99%
“…is a famous traditional Chinese medicine that exhibits antioxidative stress and neuroprotective effects (Andoh et al, 2017). is a famous traditional Chinese medicine that exhibits antioxidative stress and neuroprotective effects (Andoh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…is a famous traditional Chinese medicine that exhibits antioxidative stress and neuroprotective effects (Andoh et al, 2017). Previous studies have explored the therapeutic potential of aucubin for many other diseases, such as diabetes mellitus (Jin et al, 2008), skin fibrosis (Ho et al, 2005) and peripheral neuropathy (Andoh et al, 2017). Previous studies have explored the therapeutic potential of aucubin for many other diseases, such as diabetes mellitus (Jin et al, 2008), skin fibrosis (Ho et al, 2005) and peripheral neuropathy (Andoh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) We also showed that aucubin, which is an iridoid glycoside and the main component of Plantaginis Semen, plays an important role in the anti-allodynic action of goshajinkigan. 10) However, the mechanisms underlying the anti-allodynic activity of aucubin are not understood completely. It was reported in a previous study that paclitaxel decreased peripheral blood flow and induced mechanical allodynia in mice.…”
mentioning
confidence: 99%